소풍산물추출물이 DNCB로 유발된 접촉성피부염에 미치는 영향 - 박숙자(Sook Jahr Park); 이상곤(Sang Gon Lee); 백정한(Jung Han Baek); 변성희(Sung Hui Byun); 김상찬(Sang Chan Kim) (동의생리병리학회지, 2006)
Sopung-san(SPS; prescription No. DO27), a herbal medicine prescribed by oriental hospital of Daegu fanny University, has been used as cure for pruritus and psoriasis. To evaluate anti-inflammatory effect of Sopung-san, we treated Sopung-san extract in animal model system induced contact hypersensitivity. Contact hypersensitivity, a local inflammatory response of the skin, was induced by 1% DNCB on the right ear of BALB/C mouse. Sopung-san was prepared as water extract and administrated everyday for 2 weeks per oral. A right ear of mouse was potently swelled by 1% of DNCB treatment, but a mouse ear thickness was significantly reduced by Sopung-san after 2 weeks. treatment. Sopung-san reduced IgG in serum obtained from blood of 1 % DNCB-treated mouse. IgE in serum was not changed by DNCB and/or Sopung-san treatment. $IL-1β$ and IL-6 from ear tissue were significantly increased by DNCB, Dut were not reduced by Sopung-san. From these results, anti-inflammatory effect of Sopung-san, especially reduction of ear swelling, might be partly due to reduction of IgG in serum.